Effect of Ru/CGO versus Ni/CGO Co‐Infiltration on the Performance and Stability of STN‐Based SOFCs. Issue 6 (18th August 2014) - Ramos, T.; Veltzé, S.; Sudireddy, B. R.; Jørgensen, P. S.; Theil Kuhn, L.; Holtappels, P.
Abstract Electrolyte supported cells (ESC), with Sc2O3‐stabilized ZrO2 (ScSZ) electrolytes, Gd‐doped ceria (CGO) or M/CGO (M = Ni, Ru) infiltrated Sr0.94Ti0.9Nb0.1O3 (STN94) anodes and LSM/YSZ cathodes, were evaluated for their initial performance and long‐term stability. Power density for the Ru/CGO infiltrated cell reached ∼0.7 W cm–2 at 850 °C, 4% H2O/H2, whereas the Ni/CGO infiltrated cell reached ∼0.3 W cm–2, with the current morphologies and loadings. Operation at 0.125 A cm–2, 850 °C, feeding 50% H2O/H2 to the anode and air to the cathode, for a period >300 h, showed superior stability for the Ru/CGO infiltrated cell, with ∼0.04 mV h–1 degradation rate, when compared to the Ni/CGO infiltrated cell (∼0.5 mV h–1). For the Ni/CGO case, the observed degradation has been tentatively linked to initial changes in the electrochemical active area and long‐term detrimental interactions between components.